The concept of Road Chronotope in the Poems of Necip Fazıl Kısakürek: Images and Phenomena - Sahin, Veysel (Rector Ciu Cyprus Int Univ, 2024)
Humanity's connection to time and space becomes significant when individuals view themselves as purposeful entities within these dimensions and prioritize time and space as the ultimate, invaluable repository of memories. The most admirable occurrences, behaviors, and facts of life create their own sphere within a specific time and place. The relationship between time and space in the sphere of art and literature is complex and profound. Mikhail Bakhtin elucidates the connection and interdependence of time and space through the idea of chronotope. Mikhail Bakhtin introduces the notion of chronotope, which refers to the interconnectedness of time and place in literary works such as carnival and various genres, reflecting the unique characteristics of each genre within its narrative world. The primary function of the chronotope bond is to unveil many dimensions of time and space that embody historical liberation in societal existence. In this contex, the broadening of the chronotopical relational network in poetry generates innovative phenomena and meanings in the realm of image, metaphor, and symbol within the intricate dimensions of time and space. Necip Faztl Ktsak & uuml;rek's poems explore significant connections between time and space, incorporating major chronotopical interconnections. The road chronotope images and phenomena in Necip Faztl Ktsak & uuml;rek's poetry need the examination of the time -space relationship he constructs in his poems inside an imagined framework. Necip Faztl Ktsak & uuml;rek's poems feature chronotopes like roads and pavements that symbolize the passenger, illustrating perception, reality, intuition, fiction, and poetic connections within the concept of time -space integrity. Within this particular framework, the road and chronotopes of encounters are associated with the road in the poems of Necip Faztl Ktsak & uuml;rek. It delineates the fantastical and transcendent realms of time -space coherence, wherein the poem's subject matter, a road and pavement, elucidates its own existence.
Necip Fazıl Kısakürek’in Şiirlerinde Yol Kronotopunun İmge ve Görüngüleri
Keywords: Necip Faz & imath;l K & imath;sak & uuml;rek; poetry; chronotope; road; pavement